Inducing secondary metabolite production from Daldinia eschscholzii JC-15 by red ginseng medium. Issue 21 (1st November 2020) - Wang, Bang-Yan; Yang, Ya-Bin; Yang, Xue-Qiong; Zhu, Chen-Hao; Yang, Shuang; Xu, Ting-Ting; Wang, Xue-Yin; Tan, Ning-Hua; Zhou, Hao; Ding, Zhong-Tao
Abstract: Red ginseng (RG) is one of the most popular herbal medicines and used as a dietary supplement in recent years. The bioactive ingredient in RG can induce the production of novel microbial metabolite from fermented RG. Using the one strain-many compounds strategy, the reinvestigation of the metabolites from Daldinia eschscholzii JC-15 cultured in red ginseng medium led to the isolation of an unprecedented benzopyran-naphthalene hybrid, daldinsin (1 ) and a new lactone (2 ). In this research, a new lactone, 8-hydroxylhelicascolide A (2 ) instead of helicascolide A was produced by the D. eschscholzii JC-15 induced by the red ginseng medium. Compound 1 showed anti-acetylcholinesterase activity with the inhibition ratio of 38.8% at 50 μM. Compound 2 indicated antimicrobial activities against Fusarium Solani, F. oxysporum, and Escherichia coli with MICs at 128 μg/mL. RG is therefore a promising activator in production of novel microbial metabolite. Graphical Abstract: